Effects of a 12-Week Multimodal Exercise Intervention Among Older Patients with Advanced Cancer: Results from a Randomized Controlled Trial. (3rd February 2022) - Mikkelsen, Marta K; Lund, Cecilia M; Vinther, Anders; Tolver, Anders; Johansen, Julia S; Chen, Inna; Ragle, Anne-Mette; Zerahn, Bo; Engell-Noerregaard, Lotte; Larsen, Finn O; Theile, Susann; Nielsen, Dorte L; et al.
Abstract: Background: Older patients with cancer are at risk of physical decline and impaired quality of life during oncological treatment. Exercise training has the potential to reduce these challenges. The study aim was to investigate the feasibility and effect of a multimodal exercise intervention in older patients with advanced cancer (stages III/IV). Patients and Methods: Eighty-four older adults (≥65 years) with advanced pancreatic, biliary tract, or non-small cell lung cancer who received systemic oncological treatment were randomized 1:1 to an intervention group or a control group. The intervention was a 12-week multimodal exercise-based program including supervised exercise twice weekly followed by a protein supplement, a home-based walking program, and nurse-led support and counseling. The primary endpoint was change in physical function (30-second chair stand test) at 13 weeks. Results: Median age of the participants was 72 years (interquartile range [IQR] 68-75). Median adherence to the exercise sessions was 69% (IQR 21-88) and 75% (IQR 33-100) for the walking program. At 13 weeks, there was a significant difference in change scores of 2.4 repetitions in the chair stand test, favoring the intervention group ( p < .0001). Furthermore, significant beneficial effects were seen for physical endurance (6-minute walk test), hand grip strength, physical activity, symptom burden, symptoms of depression and anxiety, global health status (quality of life), and lean body mass. No effects were seen for dose intensity, hospitalizations, or survival. Conclusion: A 12-week multimodal exercise intervention with targeted support proved effective in improving physical function in older patients with advanced cancer during oncological treatment. Abstract : Older patients have a higher risk of physical and functional decline. This article reports a 12-week multimodal exercise-based and supportive intervention among older patients with advanced stage cancer who received systemic oncological treatment.